Reducing the Negative Impact of Job Insecurity: The Moderating Role of Perceived Employability (A Study on Contract Employees) - Adiya Alifa Yuniar; P. Tommy Y. S. Suyasa; Raja Oloan Tumanggor (Greenation Publisher & Yayasan Global Research National, 2026)
Job satisfaction is an important aspect of employee well-being and work motivation. However, maintaining job satisfaction has become increasingly challenging amid economic instability and widespread layoffs, which may increase employees’ job insecurity. This study examines perceived employability as a moderator in the relationship between job insecurity and job satisfaction among contract employees. Perceived employability refers to an individual’s ability to identify and utilize career opportunities. The study involved 121 Fixed-Term Employment Contract' (FTEC) employees.. The findings revealed a significant negative correlation between job insecurity and job satisfaction (rs = -0.371, p < 0.05). Moderation analysis showed that perceived employability tended to weaken the relationship between job insecurity and job satisfaction, although the buffering effect was not fully statistically significant. Specifically, low perceived employability showed a significant negative correlation (rs = -0.227, p < 0.1), whereas high perceived employability weakened the relationship and produced non-significant results (rs = -0.174, p > 0.05). These findings suggest that perceived employability may function as a psychological resource that helps reduce the negative impact of job insecurity under unstable employment conditions.